EXPERIMENTAL ANALYSIS OF POWER SEMICONDUCTOR ELEMENTS USED IN FLYBACK CONVERTERS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
Switch-mode power supplies (SMPS) have become very popular lately due to their superior efficiency and compact dimensions as compared to conventional counterparts which contain low-frequency transformers. This efficiency and miniaturization are connected to several factors, including high operating frequencies typically in the kHz to MHz range, the utilization of ferromagnetic materials for inductive coupling, and the incorporation of active switching components to mitigate energy loss via the Joule-Lenz effect. Enhancing SMPS efficiency implies active circuit elements (diodes, transistors, etc.) sizing and arrangements. This paper presents a practical approach by addressing a series of experiments to analyze and compare the performance of different active components. It starts with the analysis of the PWM generator module from the primary and continues with the field-effect transistors and rectifier diodes in the secondary. The asynchronous flyback topology has been chosen to carry out the experiments. By using the same experimental platform, based on the obtained results, the analysis of behavioral differences between the different components has been performed.
Keywords: Switch-mode power supply; Flyback; MOSFET; IGBT; Fast recovery diode; Schottky diode